Biofiltration of feedwater to control organic fouling of low pressure membranes. Issue 20 (18th October 2017) - Pramanik, Biplob Kumar; Roddick, Felicity A.; Fan, Linhua
ABSTRACT: The application of low pressure membrane (LPM) technology, i.e., ultrafiltration and microfiltration, for drinking water treatment and secondary effluent reclamation has increased rapidly over the past two decades. A major drawback in the use and operation of LPM processes is fouling due to the deposition of organic matter present in the feedwater on the membranes which leads to reduced water productivity necessitating membrane cleaning, process downtime and eventual membrane attrition. Pretreatment of feedwater using biological processes (particularly slow sand filtration and biological activated carbon) has been investigated as a simple and cost-effective means to control organic fouling of the membrane. In this paper, membrane fouling by the organic matter in drinking water and secondary effluent, the mechanisms of biological treatment systems, and the effectiveness of biological processes for fouling reduction are reviewed. It has been demonstrated that biological processes have great potential for controlling the organic fouling of membranes.